2019
DOI: 10.1108/jmtm-03-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

On the adoption of additive manufacturing in healthcare: a literature review

Abstract: Purpose The purpose of this paper is to discuss different 3D printing techniques and also illustrate the issues related to 3D printing and cost-effectiveness in the near future. Design/methodology/approach A systematic literature review methodology is adopted for this review paper. 3D printing is in the initial phase of implementation in healthcare; therefore, a study of 70 research papers is done, which discusses the research trends of 3D printing in healthcare sector from 2007 to mid-2018. Findings Thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 63 publications
(47 reference statements)
0
36
0
Order By: Relevance
“…There are many reviews on the medical applications of AM [ 28 , 32 , 40 , 55 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. Most of them focus on certain application areas, such as surgical instruments [ 55 ], orthopedics [ 32 ], cardiology [ 108 ], or have a material focus in certain area such as metals for prosthodontic applications [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reviews on the medical applications of AM [ 28 , 32 , 40 , 55 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. Most of them focus on certain application areas, such as surgical instruments [ 55 ], orthopedics [ 32 ], cardiology [ 108 ], or have a material focus in certain area such as metals for prosthodontic applications [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have looked at different AM processes, for example, material extrusion and binder jetting for producing pharmaceuticals [ 116 ] or ceramics for dental applications using material extrusion, binder jetting, VAT photopolymerization or powder bed fusion processes [ 111 ]. Furthermore, some only looked at the general applications of AM [ 112 ] or the whole process chain developments including, for example, the design phase [ 40 ]. There are reviews which focus on applications and even categorize those in some of the AM processes, such as VAT photopolymerization, powder bed fusion and material extrusion [ 109 , 110 ], but the other processes are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Ramola et al stated that MJ technology produces 3D models with higher accuracy than SLS or 3DP [ 83 ]. Ibrahim et al investigated the dimensional accuracy of MJ, 3DP and SLS printed mandibular anatomy parts, which showed that SLS parts had a lower dimensional error (1.79%) than MJ (2.14%) and 3DP (3.14%) parts but MJ printed parts had the highest accuracy [ 84 ].…”
Section: Process and Materialsmentioning
confidence: 99%
“…In the medical field, there are requirements for effective communication and materials. 102 Additive manufacturing is 104 This can easily create a surgical mesh which supports tissues and organ during surgery.…”
Section: Different Types Of Materials Used In Additive Manufacturing mentioning
confidence: 99%